Global monitoring report 2006 : millennium development goals : strengthening mutual accountability, aid, trade, and governance. (International Bank for Reconstruction and Development/The World Bank, 2006)
This third edition of the Global Monitoring Report examines the commitments and actions of donors, international financial institutions, and developing countries to implement the Millennium Declaration, signed by 189 countries in 2000. Many countries are off track to meet the Millennium Development Goals, particularly in Africa and South Asia, but new evidence is emerging that higher-quality aid and a better policy environment are accelerating progress in some countries, and that the benefits of this progress are reaching poor families. This report takes a closer look at the donors' 2005 commi.